Social networks and recovery (SONAR): characteristics of a longitudinal outcome study in five therapeutic communities in Australia. Issue 3 (12th September 2016) - Best, David William; Haslam, Catherine; Staiger, Petra; Dingle, Genevieve; Savic, Michael; Bathish, Ramez; Mackenzie, Jock; Beckwith, Melinda; Lubman, Dan I.
Abstract : Purpose: The purpose of this paper is to demonstrate how social identity change can support the TC objective of promoting "right living". This is compatible with the literature on addiction recovery which has shown that identity change is central to this process. While much of the earlier literature focussed primarily on an individual analysis of change, there is a growing body of research showing the important contribution that social networks, social group membership and associated social identities make to sustainable change. Design/methodology/approach: The paper describes baseline data for a multi-site prospective cohort study of 308 clients entering therapeutic community (TC) treatment and characterizes the presenting profile of this cohort on a range of social identity and recovery measures at the point of TC entry. Findings: The sample was predominantly male with a mean age of 35 years, with the large majority having been unemployed in the month before admission. The most commonly reported primary substance was methamphetamine, followed by alcohol and heroin. The sample reported low rates of engagement in recovery groups, but access to and moderate degrees of social support was also reported in the period prior to admission. Research limitations/implications: The paper highlights the important role that TCs play in facilitating identity change and in promoting sustainable recovery. Practical implications: The paper discusses opportunities for working with social identities both during residence and in community re-integration, and highlights what TCs can do to support and sustain recovery. Social implications: The paper brings to light the potential contribution of social group membership and social identity change to management of recovery in TC settings. Originality/value: The study described provides an innovative way of assessing TC effectiveness and testing novel questions about the role of social identity and recovery capital as key predictors of change.